Smartphone Application as an Education Platform in Hepato-Pancreato-Biliary Surgery. (October 2019) - Roy, Mayank; Dip, Fernando; Rosales, Armando; Roche, Matthew; Hutchins, Robert R.
Background. There are no data to assess the need for smartphone applications (SA) as an educational tool in hepato-pancreato-biliary (HPB) surgery. The primary objective of this study was to assess if SA can be used as an educational tool in HPB surgery. The secondary objective was to assess if SA can help as a decision-making tool for fellowship applicants in HPB surgery. Methods. A preapproved questionnaire was e-mailed by International Hepato-Pancreato-Biliary Association to all its 2350 members. Results. Two hundred seventy-one surgeons responded to the survey. Eight were excluded for incomplete data. A total of 48.7% of responders were between 28 and 43 years old (generation X) and 45.2% between 44 and 62 years old (baby boomers). A total of 37.6% of the responders considered SA as an effective method to teach future trainees, and there were slightly higher odds of choosing SA as a teaching tool if the responder considered themselves as an innovator (odds ratio: 2.24). A total of 87.8% of the responders believe that SA in HPB surgery can be directed toward surgical trainees' education, and 91.6% believed SA can be directed toward a fellow. Ninety-five percent of the responders believed that SA in HPB surgery can possibly help a future applicant to choose an HPB fellowship program. Conclusion . SA can complement other teaching techniques and educational tools in HPB surgery. In addition, it can potentially be used as a platform for HPB surgery fellowship by helping in making a decision regarding appropriate fellowship programs.